2018
DOI: 10.1016/j.envres.2017.12.006
|View full text |Cite
|
Sign up to set email alerts
|

Exposure to DDT and hypertensive disorders of pregnancy among South African women from an indoor residual spraying region: The VHEMBE study

Abstract: Indoor Residual Spraying (IRS), the use of insecticides inside residences for malaria control, may cause elevated exposure to insecticides such as dichlorodiphenyl trichloroethane (DDT). Evidence suggests that DDT exposure may increase blood pressure but no study has investigated associations with hypertensive disorders of pregnancy (HDP) in an IRS area. We measured the serum concentration of DDT and its breakdown product dichlorodiphenyl trichloroethylene (DDE) at the time of delivery among 733 rural South Af… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
26
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 34 publications
(27 citation statements)
references
References 33 publications
0
26
0
Order By: Relevance
“…Briefly, the 28 investigations were published between 2006–2018 with sample sizes ranging from 58 to 1.21 million women. There were 6 studies on POP (Eslami et al 2016; Murray et al 2018; Savitz et al 2012; 2014; Stein et al 2009; Starling et al 2014), one study on water contaminants (Carwile et al 2014), 11 investigations on air pollutants (Dadvand et al 2014; Lee et al 2013; Madsen et al 2017; Mendola et al 2016; Nahidi et al 2014; Pedersen et al 2017; Savitz et al 2015; Wang et al 2018b; Wesselink et al 2017; Wu et al 2016; Yorifuji et al 2015), 6 examining metals (Elongi Moyene et al 2016; Maduray et al 2017; Sandoval-Carrillo et al 2016; Laine et al 2015; Wang et al 2018a; Vigeh et al 2006), and 4 investigations evaluating non-persistent organic pollutants (Cantonwine et al 2016; Leclerc et al 2014; Ye et al 2017; Shaw et al 2018).…”
Section: Resultsmentioning
confidence: 99%
“…Briefly, the 28 investigations were published between 2006–2018 with sample sizes ranging from 58 to 1.21 million women. There were 6 studies on POP (Eslami et al 2016; Murray et al 2018; Savitz et al 2012; 2014; Stein et al 2009; Starling et al 2014), one study on water contaminants (Carwile et al 2014), 11 investigations on air pollutants (Dadvand et al 2014; Lee et al 2013; Madsen et al 2017; Mendola et al 2016; Nahidi et al 2014; Pedersen et al 2017; Savitz et al 2015; Wang et al 2018b; Wesselink et al 2017; Wu et al 2016; Yorifuji et al 2015), 6 examining metals (Elongi Moyene et al 2016; Maduray et al 2017; Sandoval-Carrillo et al 2016; Laine et al 2015; Wang et al 2018a; Vigeh et al 2006), and 4 investigations evaluating non-persistent organic pollutants (Cantonwine et al 2016; Leclerc et al 2014; Ye et al 2017; Shaw et al 2018).…”
Section: Resultsmentioning
confidence: 99%
“…Finally, we included 27 articles in this systematic review and out of 27 studies, 13 studies were included in the meta-analysis study (see Fig 1). The majority of the articles, 15 articles included in this review were cross-sectional [16,17,[22][23][24][25][26][27][28][29][30][31][32][33][34][35], nine were case-control [15,[36][37][38][39][40][41][42][43], and the remaining three were of a longitudinal study design [34,44,45]. Studies from ten countries were included in this review.…”
Section: Description Of Included Studiesmentioning
confidence: 99%
“…In addition, seasonal variation [32,43] and exposure to insecticide chemicals used for malaria control [22] were identified as associated factors for developing HDP. However, this systematic review was not found sufficient evidence to draw strong to consider as associated factor for developing HDP.…”
Section: Plos Onementioning
confidence: 99%
“…He reported that IRS was associated with elevated serum DDT/DDE and urinary pyrethroid metabolite concentrations in peripartum samples collected from 751 VHEMBE women 24,25 . Associations between maternal exposure to DDT and hypertensive disorders of pregnancy 26 , larger birth size 27 , and higher body composition measures, and marginally altered motor development were found among VHEMBE girls at age 1 and/or 2 years 28 . Prenatal exposure to pyrethroids was also associated with lower body composition measures among boys 28 and altered motor development among girls aged 1 to 3.5 years 29,30 .…”
Section: Nutrition and Toxicodietary Exposuresmentioning
confidence: 84%